DISCRIMINATION AND ANTI-IMMIGRANT ACTIVISM. THE MINUTEMAN PROJECT (Andamios, Revista de Investigación Social, 2007)
In 2005, some American groups such as Minuteman Project became famous for carrying out actions to halt illegal immigration from the southern border. Our central idea is that their political and media success have three major causes: 1) a new doctrine about U.S. National Security; 2) the re-emergence of an American “patriot” ideology whose central point is border defense, and 3) the combination of these two elements with a secular issue on the U.S.-Mexican border: anti-Mexican discrimination.
Keywords: Migration; anti-immigration american groups; Mexico-US border; US–Mexico affairs